Can the X-Factor of Teaching Be Used In Research - Hosford, Phil.; Schroder, Angela ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
For years, an intuitively perceived X-factor seemed to help principals, professors, and supervisors announce with confidence those who were "really good teachers." This study attempted to point the way to gathering data objectively with regard to the X-factor. Two specific objectives were sought. The first one was to determine to what degree the following groups of people, involved with teachers in different capacities and roles, may be in agreement on the stronger/weaker "teachers" viewed: (a) selected 9th-grade students, (b) a 9th-grade class, (c) a senior high school class, (d) masters-level students in a graduate education course, (e) full-time teachers in a graduate education course, and (f) doctoral students and professors in education. A second objective was to determine if the evaluation of prospective teachers made by the group of five 9th-graders would correlate at a high level with the other groups and be reliable enough to serve as sufficient and representative in the evaluation process of prospective teachers. All six groups evaluated the videotaped performance of sophomores involved in a microteaching assignment. The results of the collected data showed significant correlations between evaluations made by five 9th-grade students and by students in both a 9th-grade class and a senior high school class from different schools within the same district. Low correlations were found between evaluations by the five 9th-graders and graduate students, public school teachers and professors. (JA)
Microfiche.
Keywords: Administrator Attitudes; Evaluation; Evaluation Methods; Opinions; Student Attitudes; Student Teachers; Supervisors; Teacher Attitudes; Teacher Interns; Videotape Recordings; Reports, Research